2021
DOI: 10.1186/s12890-021-01568-6
|View full text |Cite
|
Sign up to set email alerts
|

LINC01089 suppresses lung adenocarcinoma cell proliferation and migration via miR-301b-3p/STARD13 axis

Abstract: Background Lung adenocarcinoma (LUAD) is one of the most common cancers with high morbidity and mortality worldwide. Long non-coding RNAs (lncRNAs) serve as tumor promoters or suppressors in the development of various human malignancies, including LUAD. Although long intergenic non-protein coding RNA 1089 (LINC01089) suppresses the progression of breast cancer, its mechanism in LUAD requires further exploration. Thus, we aimed to investigate the underlying function and mechanism of LINC01089 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(37 reference statements)
2
3
0
Order By: Relevance
“…[ 41 ].Western blot assay implied that γH2AX and Bax protein levels were upregulated and Bcl‐2 expression was downregulated in response to NPs and DDP treatment, indicating that miR‐301b‐3p Inhibitor in materials was able to enhance DDP sensitivity and induce cell apoptosis. This correlates with previous findings that miR‐301b‐3p is involved in apoptosis in cancers [ 42 , 43 , 44 ]. MiR‐301b‐3p Inhibitor and A549apt synergised more prominently than those NPs without A549apts.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[ 41 ].Western blot assay implied that γH2AX and Bax protein levels were upregulated and Bcl‐2 expression was downregulated in response to NPs and DDP treatment, indicating that miR‐301b‐3p Inhibitor in materials was able to enhance DDP sensitivity and induce cell apoptosis. This correlates with previous findings that miR‐301b‐3p is involved in apoptosis in cancers [ 42 , 43 , 44 ]. MiR‐301b‐3p Inhibitor and A549apt synergised more prominently than those NPs without A549apts.…”
Section: Discussionsupporting
confidence: 92%
“…With the help of A549apts, miR-301b-3p Inhibitor could better target cancer cells, which provides evidence in support of the finding that downregulation of miR-301b-3p increases the sensitivity of cancer cells to cisplatin as proposed by Zhu et al [41].Western blot assay implied that γH2AX and Bax protein levels were upregulated and Bcl-2 expression was downregulated in response to NPs and DDP treatment, indicating that miR-301b-3p Inhibitor in materials was able to enhance DDP sensitivity and induce cell apoptosis. This correlates with previous findings that miR-301b-3p is involved in apoptosis in cancers [42][43][44]. MiR-301b-3p Inhibitor and A549apt synergised more prominently than those NPs without A549apts.…”
Section: Wj-apt-mir Nanoparticles Regulate Proliferation Invasion Mig...supporting
confidence: 92%
“…Qian et al. ( 48 ) found that LINC01089 suppresses lung adenocarcinoma cell proliferation and migration via miR-301b-3p/STARD13 axis. Xiong et al.…”
Section: The Regulation Of Signaling Pathway That Lncrna Participated...mentioning
confidence: 99%
“…Wang et al (47) found that LINC02418 promotes malignant behaviors in lung adenocarcinoma cells by sponging miR-4677-3p to upregulate KNL1 expression. Qian et al (48) found that LINC01089 suppresses lung adenocarcinoma cell proliferation and migration via miR-301b-3p/STARD13 axis. Xiong et al (49) found that LncRNA NEAT1 may compete with USF1 for binding to miR-193a-3p as a ceRNA and accelerates lung adenocarcinoma deterioration.…”
Section: Mirna Signaling Axis 581 Mirna-3pmentioning
confidence: 99%
“…In addition to breast cancer, LNC01089 contributed to the development of other cancer types. For example, based on the study of Qian et al in 2021, in lung cancer cells, LNC01089 regulates the miR-301b-3p/STARD13 interaction axis, and through this mechanism, this lncRNA could decrease the migration rate of BC cells(Qian et al, 2021). LNC01089 also regulates the miR-27b-3p/FBLN5 axis in thyroid cancer patients, and this mechanism could suppress the malignant development(Pan et al, 2022)There has been no previous research on the diagnostic utility of LNC01089 across any cancer form, and for the rst time, we showed that this lncRNA has a signi cant diagnostic capability for distinguishing cancer samples from normal samples based on ROC analysis.…”
mentioning
confidence: 99%